Peningkatan Kapasitas Kepemimpinan Dan Minat Berwirausaha Mahasiswa Di Era Digital - Ahmad Bairizki (CV. Multi Kreasi Media, 2024)
The development of leadership capacity and entrepreneurial interest among students is a crucial aspect of creating a young generation ready to face the challenges of the digital era. This service aims to provide guidance and strategies in efforts to enhance students' leadership capacity and entrepreneurial interest through various programs and activities relevant to contemporary needs. The method used in this service involved conducting a two-day seminar with participants from Universitas Pendidikan Mandalika students, the general public, and SMEs actors in Mataram City. The series of seminars and discussions indicated that the application of digital technology in entrepreneurship education and training can increase students' interest and ability in entrepreneurship. Additionally, the development of leadership capacity through mentoring programs, workshops, and digitally-based seminars has also proven effective in enhancing students' leadership skills. This study concludes that integrating digital technology in the development of leadership capacity and entrepreneurship is a strategic step that can provide significant positive impacts for students. Proposed recommendations include increasing collaboration between universities and industries, as well as developing digital platforms for higher education institutions that support more interactive and practical entrepreneurship education and training. Thus, it is expected that students can become innovative and highly competitive leaders in this digital era.